Legal Aid Institute for the Rights of Suspects in Criminal Courts in Indonesia - Setly Selva Yuneida; Tresya Tresya; Retno Kusuma Wardani (RESAM Jurnal Hukum, 2022)
This study aims to analyze the norms related to legal aid in legislation by providing legal protection for suspects and to analyze the role of legal institution assistance in legal protection of suspects in the criminal justice system in Indonesia. The problems to be studied are the formulation of norms related to legal aid in legislation and the role of legal aid institutions in providing guarantee protection for suspects in the criminal justice system in Indonesia. This study uses a normative juridical approach by collecting primary, secondary and tertiary data. This study uses a conceptual approach and data analysis techniques by interpreting, assessing and evaluating. Based on this study, it was found that in the Criminal Procedure Code there are legal aid norms, which still have contradictions with other norms (contradiction determins), as well as the provisions governing the role of legal aid, in this case, legal aid institutions have not played a good role, so many the suspect's rights are still neglected during the examination process.